Tg(Δ113p53:cmyc) Transgene Upregulates glut1 Expression to Promote Zebrafish Heart Regeneration - Zimu Tang; Kaiyuan Wang; Lijian Lo; Jun Chen (Journal of Cardiovascular Development and Disease, 2023)
The heart switches its main metabolic substrate from glucose to fatty acids shortly after birth, which is one of reasons for the loss of heart regeneration capability in adult mammals. On the contrary, metabolic shifts from oxidative phosphorylation to glucose metabolism promote cardiomyocyte (CM) proliferation after heart injury. However, how glucose transportation in CMs is regulated during heart regeneration is still not fully understood. In this report, we found that the expression of Glut1 (slc2a1) was upregulated around the injury site of zebrafish heart, accompanied by an increase in glucose uptake at the injury area. Knockout of slc2a1a impaired zebrafish heart regeneration. Our previous study has demonstrated that the expression of Δ113p53 is activated after heart injury and Δ113p53+ CMs undergo proliferation to contribute to zebrafish heart regeneration. Next, we used the Δ113p53 promoter to generate the Tg(Δ113p53:cmyc) zebrafish transgenic line. Conditional overexpression of cmyc not only significantly promoted zebrafish CM proliferation and heart regeneration but also significantly enhanced glut1 expression at the injury site. Inhibiting Glut1 diminished the increase in CM proliferation in Tg(Δ113p53:cmyc) injured hearts of zebrafish. Therefore, our results suggest that the activation of cmyc promotes heart regeneration through upregulating the expression of glut1 to speed up glucose transportation.